Barriers and enablers to measuring resting metabolic rate in the high-performance sporting system: A qualitative exploratory study - Kuikman, M. A.; McKay, A. K. A.; Brown, H.; Townsend, N.; McCormick, R.; Morabito, A.; Pichshev, N.; Slater, G.; Burke, L. M. (Journal of Sports Sciences, 2025)
Measurements of resting metabolic rate (RMR) may be undertaken for dietary planning purposes or to assess for low energy availability (LEA). This study investigated barriers and enablers to measuring RMR in real-world, high-performance sport environments. Twelve interviews were conducted with technicians (n = 6 dietitians, n = 6 physiologists) employed across six National Institute Networks, two National Sporting Organisations and one professional sporting code. RMR was predominantly measured to screen for LEA with measurements only occurring in a few instances for dietary planning purposes. Data was thematically analysed with six main themes identified. Barriers included lack of confidence in measuring RMR, burden of measurement on athlete and technician, confusion over measurement responsibility, and scepticism in RMR measurements as an indicator of LEA. Subthemes that contributed to scepticism included: the RMR thresholds used to indicate LEA, unanswered research questions, and measurement errors introduced by athlete presentation, testing equipment and/or environment. Enablers to use of RMR measurements included perceived value of RMR measurements as a `piece of the puzzle` when assessing for LEA and its use as a longitudinal measure. Best practice guidelines for RMR measurements in athletic cohorts must consider these barriers and enablers as they highlight unique characteristics of athletes and their environment.